2018
DOI: 10.1155/2018/1856109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Physicochemical Characterization of Anion Exchanger Based on Green Modified Bottle Gourd Shell

Abstract: The structural performance and biosorption behavior of a new cationic biosorbent (CALV) prepared from bottle gourd (Lagenaria vulgaris) shell (LVS) as a potentially valuable agrowaste have been established. The biosorbent with anion exchangeable function was synthesized from a modified lignocellulosic biomass (MLV) by a quaternary ammonium agent, N-(3-chloro-2-hydroxypropyl)trimethylammonium chloride. Preparation of the appropriate MLV precursor was firstly carried out by the process of alkaline pretreatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In this way, the availability of various chemical agents to the cellulose chain increases. These findings were confirmed by FTIR spectroscopic and SEM-EDS morphological analysis of biomass samples before (LVS) and after (LVSAT) the pretreatment procedure [37].…”
Section: Schematic Presentation Of Lvs Biomass Pretreatment (A) and C...supporting
confidence: 60%
See 2 more Smart Citations
“…In this way, the availability of various chemical agents to the cellulose chain increases. These findings were confirmed by FTIR spectroscopic and SEM-EDS morphological analysis of biomass samples before (LVS) and after (LVSAT) the pretreatment procedure [37].…”
Section: Schematic Presentation Of Lvs Biomass Pretreatment (A) and C...supporting
confidence: 60%
“…The partner of this IR band (from the asymmetric C-N bond) is located at about 980 cm −1 , suggesting the presence of new -CH 3 groups. All these observations clearly indicate the incorporation of the cationic -N + R 3 group on the LVSAT-CHMAC biosorbent surface during biomass modification [4,6,37].…”
Section: Reaction Path Of the Cationic Lvsat-chmac Sorbent Synthesis:...mentioning
confidence: 68%
See 1 more Smart Citation
“…However, it should be noted that these bands, together with a deformation vibration band of OH group (in plane) at 1423 cm -1 and a wide band of the vibration of the cellulose ester group at 1260 cm -1 , are correlated with the crystalline cellulose structure [43]. Thus, the apparently small changes in band intensity indicate a 8(2) (2019) [46][47][48][49][50][51][52][53][54][55][56][57] proportional change in the fraction of the crystalline to amorphous form of certain cellulose areas in the treated sample, which favors more efficient sorbent synthesis based on this precursor.…”
Section: (2) (2019) 46-57mentioning
confidence: 99%
“…Consequently, modified resins are more suitable than conventional commercial ones for recovering a specified metal ion with high selectivity . Several studies have been reported for polymeric supports in which an inert support is integrated with a selective chelating agent to produce a solid sorbent used to separate uranium from dilute aqueous solutions …”
Section: Introductionmentioning
confidence: 99%